Control Of High Gain Converter - Mugundhan S,; Arounassalame M, (International Journal of Scientific Research in Science and Technology, 2025)
Nowadays, because of pollution problems of the conventional energy resources and their unpleasant effects on the earth planet and people life, renewable resources such as photovoltaic(PV) cells and fuel cells are considered to produce electrical energy. These sources directly convert solar energy into electrical energy. Since, the output voltage of PV cells is low; a high gain boost DC-DC converter is needed to increase the low voltage so as to produce high dc output voltage. In this work, a unique high boost DC-DC converter is considered. This converter has higher voltage gain compared to the conventional boost converters. For conventional boost converter, in order to obtain high voltage gain, the extreme duty ratio of its switch is required, which increases the input current ripple greatly. Meanwhile, the power component suffers high voltage stress and work in hard switching condition, bringing about serious conducting losses and reduces the conversion efficiency. The converter used in the present study has network of switched inductor and switched capacitor and can achieve high voltage gain under appropriate duty cycle. Meanwhile, the active switches and diodes suffer from low voltage stress. In this paper, a control scheme is proposed for this non-isolated high step-up dc-dc converter. A closed loop scheme is developed using PI controller. The circuit simulation is done using MATLAB/Simulink. The performance of the high gain converter with PI controller is analyzed and the results are presented.